Static Magnetic Field Accelerates Wound Healing by Activation PI3K/AKT/mTOR Signaling Pathway - Zhong, Shuyan; Bai, Zan; Wu, Juan; Wu, Menglu; Zhang, Ren-Jian-Zhi; Lai, Rongguang; Zheng, Xinnan; Shu, Maoguo; Du, Huicong (Current Medicinal Chemistry, 2025)
<span class=
Keywords: PI3K/AKT/mTOR pathway